Regulation of iron homeostasis through the erythroferrone‐hepcidin axis in sickle cell disease. (6th February 2020) - Mangaonkar, Abhishek A.; Thawer, Fahim; Son, James; Ajebo, Germame; Xu, Hongyan; Barrett, Nadine J.; Wells, Leigh G.; Bowman, Latanya; Clair, Betsy; Patel, Niren; Bora, Pritam; Jung, Grace; et al.
Summary: Sickle cell disease (SCD) has a distinct pattern of transfusional iron overload (IO) when compared to transfusion‐dependent β‐thalassaemia major (TDT). We conducted a single institution prospective study to evaluate plasma biomarkers of iron regulation and inflammation in patients with SCD with IO (SCD IO cases, n = 22) and without IO (SCD non‐IO cases, n = 11), and non‐SCD controls ( n = 13). Hepcidin was found to be inappropriately low, as evidenced by a significantly higher median hepcidin/ferritin ratio in non‐SCD controls compared to SCD IO cases (0·3 vs. 0·02, P < 0·0001) and SCD non‐IO cases (0·3 vs. 0·02, P < 0·0001), suggesting that certain inhibitory mechanism (s) work to suppress hepcidin in SCD. As opposed to the SCD non‐IO state, where hepcidin shows a strong significant positive correlation with ferritin (Spearman ρ = 0·7, P = 0·02), this correlation was lost when IO occurs (Spearman ρ = −0·2, P = 0·4). Although a direct non‐linear correlation between erythroferrone (ERFE) and hepcidin did not reach statistical significance both in the IO (Spearman ρ = −0·4, P = 0·08) and non‐IO state (Spearman ρ = −0·6, P = 0·07), patients with highest ERFE had low hepcidin levels, suggesting that ERFE contributes to hepcidin regulation in some patients. Our results suggest a multifactorial mechanism of hepcidin regulation in SCD.